Transcranial Direct-Current Stimulation and Behavioral Training, a Promising Tool for a Tailor-Made Post-stroke Aphasia Rehabilitation: A Review - Zettin, Marina; Bondesan, Caterina; Nada, Giulia; Varini, Matteo; Dimitri, Danilo (Frontiers in Human Neuroscience, 2021)
Aphasia is an acquired language disorder resulting from damage to portions of the brain which are responsible for language comprehension and formulation. This disorder can involve different levels of language processing with impairments in both oral and written comprehension/production. Over the last years, different rehabilitation and therapeutic interventions have been developed, especially non-invasive brain stimulation (NIBS) techniques. One of the most used NIBS in aphasia rehabilitation is the Transcranial Direct-Current Stimulation (tDCS). This technique has been proven to be effective in promoting a successful recovery in both the short and long term after a brain injury. The main strength of tDCS is its feasibility associated with relatively minor side effects, if safely and properly administered. The tDCS technique requires two electrodes, an anode and a cathode, which are generally placed on the scalp. The electrode montage of tDCS can be either unipolar or bipolar. The main aim of this review is to give an overview of the state of the art of tDCS for aphasia. The studies described included patients with different types of language impairments, with non-fluent aphasia, and in several cases anomia. The effects of tDCS are variable and depend on several factors, such as electrode montage and size, duration of the stimulation, current density and characteristics of the brain tissue underneath the electrodes. Generally, tDCS has often led to promising results in rehabilitating patients with acquired aphasia, especially if combined with different language and communication therapies. The selection of the appropriate approach depends on the impaired language function. When used in combination with treatments such as Speech and Language Therapy, Constraint Induced Aphasia Therapy or Intensive Action Treatment, tDCS has generally promoted a better recovery of the impaired functions. In addition to rehabilitation protocols, Action Observation Therapy, such as IMITAF, may contribute to the reduction of post-stroke anomia. The potential of combining such techniques with tDCS would therefore be a possibility of further improvement, also providing the clinician with new action and intervention tools. The association of a tDCS protocol with a dedicated rehabilitation training would favor a generalized long-term improvement of the different components of language.